2000
DOI: 10.1093/nar/28.1.173
|View full text |Cite
|
Sign up to set email alerts
|

The RDP (Ribosomal Database Project) continues

Abstract: The Ribosomal Database Project (RDP-II), previously described by Maidak et al., continued during the past year to add new rRNA sequences to the aligned data and to improve the analysis commands. Release 7.1 (September 17, 1999) included more than 10 700 small subunit rRNA sequences. More than 850 type strain sequences were identified and added to the prokaryotic alignment, bringing the total number of type sequences to 3324 representing 2460 different species. Availability of an RDP-II mirror site in Japan is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
326
0
2

Year Published

2001
2001
2021
2021

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 528 publications
(328 citation statements)
references
References 5 publications
0
326
0
2
Order By: Relevance
“…The sequences were aligned to the Ribosomal Database Project (RDP) small subunit rRNA alignment version 7.1 (26), running locally in the ARB sequence environment (4). The RDP 7.1 alignment comprises 7,008 entries of mostly full-length or partial sequences for the Bacteria domain.…”
Section: Methodsmentioning
confidence: 99%
“…The sequences were aligned to the Ribosomal Database Project (RDP) small subunit rRNA alignment version 7.1 (26), running locally in the ARB sequence environment (4). The RDP 7.1 alignment comprises 7,008 entries of mostly full-length or partial sequences for the Bacteria domain.…”
Section: Methodsmentioning
confidence: 99%
“…Phylogenetic analysis-Preliminary analyses using BLAST searches (Altschul et al 1990) of genbank and sequence match in the ribosomal database project (RDP; Maidak et al 2000)] showed that the organisms most closely related to strain BLI-41 are members of the genus Vibrio. Aligned sequences of representative Vibrios and relatives were downloaded from RDP, and additional sequences from Genbank were added to the alignment and aligned by eye using Sequencher (Gene Codes).…”
Section: Identification Of a Natural Desferrioxamine Siderophore Prodmentioning
confidence: 99%
“…The resulting 16S rDNA sequence was compared with RDP (Maidak et al, 2000) and EMBL (Baker et al, 2000) database sequences to find the most closely related species. For phylogenetic analysis we used 18 data sets of sulfate-reducing bacteria and Escherichia coli as the prokaryotic outgroup.…”
Section: Methodsmentioning
confidence: 99%